2017
DOI: 10.1007/s11010-017-3000-6
|View full text |Cite
|
Sign up to set email alerts
|

CLDN-1 promoted the epithelial to migration and mesenchymal transition (EMT) in human bronchial epithelial cells via Notch pathway

Abstract: Claudin-1 (CLDN-1) is one of main tight junction components that play an important role in epithelial-mesenchymal transition (EMT). However, the effects of CLDN-1 on the migration and EMT induced by TGF-β1 in primary normal human bronchial epithelial (NHBE) and BEAS-2B cells have not been clear. The expression of CLDN-1 was quantified by Western blotting in NHBE and BEAS-2B cells. Cell migration and invasion were detected using transwell assays. The expression level of E-cadherin, N-cadherin, α-SMA, and Viment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Extensive studies have demonstrated that the Notch signaling pathway is also critical for EMT in tumorigenesis and fibrogenesis. The overexpression of Notch1‐induced EMT in PC‐3 cells, and claudin‐1 contributed to EMT by the Notch signaling pathway in human bronchial epithelial cells . In addition, Notch and TGF‐β1 generated a reciprocal positive regulatory loop and cooperatively regulated EMT in epithelial ovarian cancer cells, which provided new insight into the mechanism of EMT .…”
Section: Small Molecules Against Emtmentioning
confidence: 96%
See 1 more Smart Citation
“…Extensive studies have demonstrated that the Notch signaling pathway is also critical for EMT in tumorigenesis and fibrogenesis. The overexpression of Notch1‐induced EMT in PC‐3 cells, and claudin‐1 contributed to EMT by the Notch signaling pathway in human bronchial epithelial cells . In addition, Notch and TGF‐β1 generated a reciprocal positive regulatory loop and cooperatively regulated EMT in epithelial ovarian cancer cells, which provided new insight into the mechanism of EMT .…”
Section: Small Molecules Against Emtmentioning
confidence: 96%
“…The overexpression of Notch1-induced EMT in PC-3 cells, and claudin-1 contributed to EMT by the Notch signaling pathway in human bronchial epithelial cells. 180,181 In addition, Notch and TGF-β1 generated a reciprocal positive regulatory loop and cooperatively regulated EMT in epithelial ovarian cancer cells, which provided new insight into the mechanism of EMT. 182 Moreover, miR-34a downregulation induced by hypoxia enhanced EMT via the Notch signaling pathway in tubular epithelial cells, which indicated that the Notch signaling pathway is critical for EMT during fibrosis.…”
Section: Notch Signaling Pathwaymentioning
confidence: 99%
“…S3) and it is possible to assume that there were some PECs in the podocyte cluster. However, PECs are also known to undergo EMT and these markers are also reported to be involved in the EMT process 29,30,31,32,33 and are also highly expressed in tubular and collecting ductal cell clusters, making it challenging to confirm their presence in the current study.…”
Section: Discussionmentioning
confidence: 92%
“…2B and C ). α-SMA is a marker of EMT ( 26 ), and FN and COL-1 are ECM markers ( 27 ). Therefore, the effect of MIAT knockdown on the protein expression levels of α-SMA, FN and COL-1 was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence has suggested that the ERK signaling pathway is associated with the development of multiple diseases ( 26 ). For example, one study reported that ERK signaling was activated during the development of Kashin-Beck disease ( 37 ).…”
Section: Discussionmentioning
confidence: 99%